Estresse percebido e a associação com dismenorreia primária em mulheres brasileiras: estudo transversal - Moraes, Pâmela Calixto (Universidade Federal de São Carlos, 2024)
Perceived stress is when the person can report their feelings and sensations due to the interference of stress in their daily activities. Prior studies indicate that perceived stress is associated with Primary Dysmenorrhea (PD) in different countries. However, in Brazil we still do not have a study about PD and perceived stress. This study aims to evaluate the association between perceived stress and PD in Brazilian women. Methods: We used data from 2504 participants, a prospective cohort of Brazilian women. The eligibility was restricted to women who had their last three periods and were over 18 years, the exclusion criteria was 1) women with secondary dysmenorrhea and that did not have a period. We measured stress with the Perceived Stress Scale; the interference of PD with the Dysmenorrhea Symptom Interference, and the PD with the Numerical Rating Score. Results: The average perceived stress score was 25.1 ± 6.6, and the average menstrual pain in the last period was 5.1 ± 2.8. After the association analysis, logistic regression analysis was considered to determine the variables that were associated with perceived stress. Women with PD are 1.33 times more likely to have perceived stress OR (1.33; 95% IC 1.03 – 1.71) and in women with severe interference of PD, there was almost a 3-fold increase in the chance to report perceived stress (2.91; 95% IC 1.69 – 5.02). Conclusions: Women with PD have a significant association with perceived stress in Brazilian women. The higher the intensity of menstrual pain, the greater the number of Brazilian women who report mild to high stress.
Perceived stress is associated with primary dysmenorrhea in brazilian women: a cross-sectional study
Keywords: Ciclo menstrual; Dismenorreia primária; Estresse percebido; Qualidade de vida; Saúde da mulher; Menstrual cycle; Primary dysmenorrhea; Perceived stress; Quality of life; Women’s health; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL